Nilai-Nilai Budaya Dalam Kumpulan Cerita Rakyat Daerah Sumatera Utara Karya Bambang Suwondo: Kajian Antropologi Sastra - Annisa Putri Maharani Lubis; Hariadi Susilo; Emma Marsella (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2025)
As an intangible cultural heritage, North Sumatran folktales embody noble values that have yet to be systematically mapped in academic studies. This research aims to identify and analyze the cultural values embedded in a collection of North Sumatran folktales by Bambang Suwondo through a literary anthropology approach. A descriptive qualitative method was employed using literature study techniques. The data, consisting of narrative excerpts and dialogues, were analyzed using a semiotic-anthropological reading technique that identifies symbols, metaphors, and narrative patterns representing cultural values. The findings categorize cultural values into three main areas: (1) human relationships with society (mutual cooperation, wisdom, justice, deliberation); (2) human relationships with others (helpfulness, affection, obedience, compassion); and (3) human relationships with oneself (responsibility, perseverance, honesty, hard work). These findings affirm that North Sumatran folktales function not only as entertainment but also as a medium for the transmission of cultural values essential to character and identity formation, thereby holding strong relevance for character education among younger generations